The development of the heirs of young smart farmers according to the King's philosophy - สมณาศักดิ์, วราดวง; Chirinung, Pensri; Sirisunhirun, Somboon; Pintobtang, Prapart (CRRU Law, Political Science and Social Science Journal, 2021)
This article aims to present the development of young smart farmers heirs according to the royal science to be in line with the economic structure of Thailand 4.0, emphasizing the principles of the King's philosophy "understanding, accessing, developing" consisting of 1) Understanding means Self-understanding and having positive attitude of the heirs of young smart farmers 2 ) Accessing means access to policies to support the heirs of young smart farmers and networking and 3) Development consists of 3 areas of development: information technology and agricultural innovation, management and leadership of the heirs of young smart farmers.